Competing Visions of World Order Global Moments and Movements, 1880s-1930s - Conrad, Sebastian; Sachsenmaier, Dominic; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
Bringing together scholars from around the world, this first book in the Palgrave Macmillan Transnational History Series raises the question of how we can get away from the contemporary language of globalization, so as to identify meaningful, global ways of defining historical events and processes in the late Nineteenth and Twentieth centuries.
Keywords: Imperialism; World history; Civilization—History.; Historiography; History, Modern; Imperialism and Colonialism; World History, Global and Transnational History; Cultural History; Historiography and Method; Modern History